Effects of an adapted physical education training package on special education teacher instruction. (16th November 2018) - Laughlin, Michael K.; Murata, Nathan M.; McDougall, Dennis
Abstract : This study investigated the impact of an adapted physical education training package on functional motor skill instruction of three special education teachers who instructed secondary students with low‐incidence disabilities. The training package emphasized teachers' use of systematic prompting and specific reinforcement teaching strategies plus adapted physical education consultation. We used a multiple baseline design and collected data on the three teachers' use of systematic prompting and specific reinforcement plans during videotaped teaching trials. We also collected data on how teachers documented their instructional strategies, and we analyzed personal reflections that teachers wrote in the journals. Results indicated that with each of the three teachers, correctly implemented functional motor skill instructional performance improved after they completed the training package.